Designed to Impress : With an Edition of Madrid MS 2908. - Bell, Janis Callen (Vernon Art and Science Inc., 2023)
The book explores the works of Guido Mazenta, specifically his plans for the entry of Gregoria Maximiliana of Austria into Milan in 1597. It provides an in-depth analysis of Mazenta's architectural and artistic designs, his friendships with men of learning, and his prominence as a collector of art. It also examines the political and social contexts of the time, including the Austrian and Spanish Habsburgs and their marriages. The book aims to shed light on a significant event in world history and Mazenta's role in it. Its intended audience includes students and scholars of history, architecture, and art.
Description based upon print version of record.
Keywords: Mazenta, Guido, -- -1613.; Triumphal arches -- Italy -- Milan -- History -- 16th century.; Public sculpture -- Italy -- Milan -- History -- 16th century.; Arcs de triomphe -- Italie -- Milan -- Histoire -- 16e siècle.; Sculpture publique -- Italie -- Milan -- Histoire -- 16e siècle.; Public sculpture; Triumphal arches; Italy -- Milan; 1500-1599; History